Different types of salt on kimchi fermentation: Implementation of bibliometry using publish or perish and VosViewer - Fannisa Hafidhia Suryana (Jurnal Teknik Industri, Sistem Informasi dan Teknik Informatika, 2023)
Kimchi is a typical Korean food that is crucial for Korean people to consume. This food is processed through lactic acid fermentation which can give it a sour taste. The sour taste is due to a decrease in pH <7. Research on kimchi has been carried out previously with different variables. To determine the novelty of what is being researched, it can be seen from keywords related to the results of literature studies of journal articles related to the focused research. In connection with the research objective, namely to determine the differences in types of salt on kimchi fermentation by utilizing the bibliometric method using Vosviewer software. By mapping the data produced from Vosviewer, keywords will be generated that can be used to obtain gaps in the research to be carried out.